Law Relating to Procedure for Providing Maintenance in India: An analysis of maintenance laws and procedures for women in India (Journal of Advances and Scholarly Researches in Allied Education, 2021)
This article discusses different laws regarding the procedure for providing maintenance towomen in India. This is a descriptive study based on secondary research. It studies the Section 488 (8)Code of Criminal Procedure, 1898 that talks about maintenance. The paper discusses provisions ofSection 125 of the Code of Criminal Procedure, 1973. It compares the former law with the present law. Itstudies the different scenarios of dissolution of marriage vis a vis right of maintenance to wife andchildren in different cases. The paper also explains the procedural aspect to obtain Maintenance,according to Section 125 of the Cr.PC,1973.